DNA on drugs (part 2): An extended study into the transfer and persistence of DNA onto illicit drug capsules using realistic scenarios. (September 2022) - Griffin, Amy; Kirkbride, K. Paul; Henry, Julianne; Painter, Ben; Linacre, Adrian
Abstract: Capsules are now the main form of ecstasy rather than tablets in Australia and therefore their examination is of interest to forensic drug chemists in Australia and possibly elsewhere. Recently, we used controlled experimental conditions to show that capsules may be a source of DNA that can be used to identify those involved in production and distribution of illicit drugs. The question remains: in realistic scenarios where there are more unknowns, can we still detect DNA, and determine whose it is, on the exterior of capsules? The concept of comprehensive forensic intelligence and investigations – utilizing both biological and chemical signatures – relating to illicit drug preparations (i.e., the capsules and their contents) may be of great use to law enforcement. Experiments were conducted with both semi-realistic and realistic scenarios where two volunteers were asked to firstly use an encapsulator and mimic the loading of capsules, then Volunteer 1 would count out the capsules that Volunteer 2 prepared, and vice versa. This was to simulate the scenario where one person was involved in the assembly of the capsules which were then separated into smaller bags of 10 capsules by a second person for distribution. Gelatine and vegetable capsules were tested, with 10 replicates used per capsule type, scenario, and volunteer (total n = 80 capsules). Volunteer 2 was included as a contributor to the DNA profiles generated from 100% of samples handled by them within the semi-realistic scenario, whereas the other volunteer could be included as a contributor in 65% of samples. For the realistic scenario, profiles could be generated with the inclusion of both volunteers as profile contributors in 15% of samples and from just one of the volunteers in a further 50% of samples (therefore in total, either both or one of the volunteers were detected in 65% of realistic samples). Surprisingly, it was not necessarily the case that the last person to handle the capsule was the major or only contributor. The potential variability in the DNA quantities that could be deposited onto the capsules of genuine illicit drugs is high and would vary on a case-by-case basis. Nevertheless, this study has indicated that in realistic scenarios where two people are involved in the later stages of illicit drug capsule preparation, that either one or both individuals may be identified, potentially opening new investigative leads for law enforcement agencies as well as offering new information for intelligence-led policing. Highlights: Investigated transfer and persistence of DNA onto capsules in two scenarios. Mimicked ecstasy preparation with single handlers and encapsulator (semi-realistic). Mimicked ecstasy preparation involving two handlers (realistic). One or both individuals were detected in 65% of realistic samples. The last person to handle the capsule was not always major contributor.